(untitled) (Fiep Bulletin - online, 2015)
The aim of this study was to verify if it has association of the incidence of URTI with the fact to practice swimming in indoor and outdoor swimming pool, and with sedentary. The instrument for 120 voluntary individuals of both was used the genders, being 40 swimmers in indoor swimming pool, 40 swimmers in outdoor swimming pool and 40 sedentary, that they tell to its signals and symptoms of infections for a period of thirty and one days, classifying between light, moderate and severe signals the symptoms. The collected data had been quantified with punctuation to evaluate the incidence of infections of the superior respiratory treatment. The counting of episodes of infections of the superior respiratory treatment of the period of study of each individual in each group was made. The incidence of infections of the superior respiratory treatment was not different significantly between the groups. We concluded that the incidence of infections of the upper superior tract infection does not have relation with the environment of the swimming pool where if it swims (indoor or outdoor) and with the practice swimming in moderate intensity for this weather in this time of the year in the city of Belo Horizonte.